Acetaminophen elevates unbound bilirubin levels by the glucose oxidase‐peroxidase method. Issue 9 (30th July 2021) - Ichimura, Shintaro; Kakita, Hiroki; Asai, Shimpei; Mori, Mari; Takeshita, Satoru; Ueda, Hiroko; Kondo, Tomoko; Ohashi, Wataru; Okumura, Akihisa; Yamada, Yasumasa
Abstract: Background: Acetaminophen is widely administered to neonates but its effect on unbound bilirubin (UB) levels remains unclear. The aim of this study was to clarify whether administration of acetaminophen is related to an elevation of UB levels. Method: Infants with a birthweight of ˂1, 500 g admitted to our neonatal intensive care unit between January 2017 and April 2020 were retrospectively reviewed. Seventy‐one infants were enrolled, five of whom had received acetaminophen. Clinical data were analyzed when the highest UB value (UB peak) in each infant was recorded. Demographic data and information on treatment within the 24 h before the UB peak were also collected. UB was determined by the glucose oxidase‐peroxidase (GOD‐POD) method. Infants were categorized according to the presence or absence of acetaminophen administration (acetaminophen and no acetaminophen groups) within 24 h of the UB peak. The relationship between UB values and various clinical variables was then compared. Results: Both the peak UB value and the ratio of gastrointestinal disease were higher in the acetaminophen group than in the no acetaminophen group. Univariate analysis revealed that a total of seven variables were potentially correlated with UB peak values ( P  < 0.10). Multivariate analysis showed that acetaminophen and direct bilirubin were independently associated with UB peak values. Conclusion: Our study suggests that administration of acetaminophen is related to higher UB levels by the GOD‐POD method. UB values measured by the GOD‐POD method should not be used in infants treated with acetaminophen for evaluation of bilirubin neurotoxicity avoidance.